Development of scholastic well-being in the course of the 5th grade in secondary education - Obermeier, Ramona; Gläser-Zikuda, Michaela (International Journal of Educational Research, 2022)
Scholastic well-being is highly relevant, as it is connected with achievement and successful coping with critical life events. Since well-being in school is a multidimensional construct, it is necessary to analyze trajectories of these multiple dimensions to get a deeper understanding of changes and influencing factors. The empirical base for differential development of scholastic well-being for girls and boys, students with and without migration background and students attending medium and academic educational tracks is inconsistent. Additionally, there is a lack of findings regarding students' well-being in co-educational versus single-sex schools. Therefore, the current study aims at analyzing changes in all six dimensions of scholastic well-being during the 5th grade for specific groups of students (boys and girls, students with and without migration backgrounds, students attending medium and academic educational tracks and in co-educational versus singlesex schools). Based on a sample of N = 1,042 students in Catholic schools (80.5% female, 25.8% with migration background, 48.9% in a medium educational track, 54.3% in single-sex schools) who participated in three measurement time points, longitudinal multi-level analyses were calculated. Results reveal a decrease in all dimensions of scholastic well-being over time. Additionally, they illustrate the causal role of time-stable covariates, such as gender, educational track, migration background, and co-educational versus single-sex schooling. The results show slightly different trajectories for male and female students. Thus, the presented study builds upon results of previous studies by providing further information on short-term changes of scholastic wellbeing and different trajectories for specific groups of students.
CRIS-Team WoS Importer:2022-05-27